Imaging of the temporomandibular joint. Issue 1 (January 2021) - Whyte, A.; Boeddinghaus, R.; Bartley, A.; Vijeyaendra, R.
Abstract : Temporomandibular disorders are common, especially in young to middle-aged women, and most settle with supportive treatment. Imaging is indicated for the small percentage of cases that do not respond to conservative management and when the diagnosis is no doubt. The temporomandibular joint (TMJ) is a bilateral synovial articulation between the mandible and skull base. It has an intra-articular disc dividing the joint into superior and inferior compartments and the articular surfaces are lined with fibrocartilage. The normal imaging anatomy of the TMJ is described and illustrated. Different movements occur in each joint compartments: a hinge movement in the inferior joint space and translation or gliding in the superior joint space. Internal derangement is the commonest disorder affecting the TMJ and is most commonly due to disc displacement, followed by osteoarthritis and inflammatory arthritides. The imaging findings, primarily on magnetic resonance imaging (MRI) and computed tomography (CT), of internal derangement and less common disorders of the joint, are reviewed and illustrated. Optimal imaging protocols are discussed with detailed reporting guidelines.